2023
DOI: 10.1001/jamanetworkopen.2023.8908
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Disadvantage and Breast Cancer–Specific Survival

Abstract: ImportanceNeighborhood-level disadvantage is an important factor in the creation and persistence of underresourced neighborhoods with an undue burden of disparate breast cancer–specific survival outcomes. Although studies have evaluated neighborhood-level disadvantage and breast cancer–specific survival after accounting for individual-level socioeconomic status (SES) in large national cancer databases, these studies are limited by age, socioeconomic, and racial and ethnic diversity.ObjectiveTo investigate neig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Prior studies have identified that neighborhood disadvantage is associated with later stage at presentation, triple negative BC, and shorter survival in women with BC 4,8,30,31 . Disadvantaged neighborhoods are associated with marginalized populations, as economic and residential segregation has roots in structural racism 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have identified that neighborhood disadvantage is associated with later stage at presentation, triple negative BC, and shorter survival in women with BC 4,8,30,31 . Disadvantaged neighborhoods are associated with marginalized populations, as economic and residential segregation has roots in structural racism 32 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, most studies linking neighborhood disadvantage to shorter BC survival attribute this association to disparities in access to care 3–6 . However, recent studies have identified that disparities in BC survival remain between women living in disadvantaged compared with advantaged neighborhoods, even after controlling for multilevel access to care barriers, individual-level factors, tumor characteristics, and receipt of National Cancer Center Network guideline-concordant treatment 7,8 . This suggests unaccounted mechanisms that contribute to persistent BC survival disparities by neighborhood disadvantage.…”
mentioning
confidence: 99%
“…Specifically, studies have shown associations with neighborhood disadvantage, lower neighborhood socioeconomic status, and geospatial measures of economic residential segregation with shorter breast cancer survival after controlling for many of the individual-level, neighborhood-level, and structural factors that have been associated with shorter breast cancer survival in previous literature. This residual association of neighborhood disadvantage with survival suggests that there are underlying mechanisms by which neighborhood disadvantage impacts survival that have not been accounted for . Many of these studies are limited to specific geographic areas, limiting the generalizability of the study on a national level, or have limitations based on population choice, such as older Medicare patients with fee-for-service coverage, so results may not be generalizable to younger patients or those with other types of insurance …”
Section: Introductionmentioning
confidence: 99%
“…Racial and ethnic disparities in health reflect structural differences across social factors and resources, including environmental factors and access to health care interventions . Prevailing evidence suggests that disparities in cancer treatment and mortality associated with individuals’ race and ethnicity are not fully accounted for by individual-level, clinical, and demographic factors and that neighborhood factors influencing health and health care access could be contributors …”
Section: Introductionmentioning
confidence: 99%
“…There has been growing interest in how area-level measures of socioeconomic status and environment are associated with health outcomes. Area-level measures have been associated with frailty, obesity, and cardiovascular disease as well as access to preventive health care in historically marginalized populations . In regard to cancer-specific outcomes, a higher Social Vulnerability Index (SVI) score has been associated with patients being less likely to receive neoadjuvant chemotherapy or to use high-volume centers for surgical resection and with patients being more likely to encounter fragmented postoperative care .…”
Section: Introductionmentioning
confidence: 99%